Morphological and Molecular Analysis and Flowering Time of T2 Generation Transgenic Rice cv. Nipponbare Carrying CONSTANS (CO) Gene - Irshanty, Firdha Meidi; Salamah, Andi; Santoso, Tri Joko (Makara Journal of Science, 2014)
Flowering is an important process that initiates plant productivity. Rice (Oryza sativa cv. Nipponbare) was genetically engineered by introducing a CONSTANS (CO) gene from Arabidopsis thaliana (AtCO) to improve rice productivity. The CO gene is a gene responsible for inducing early flowering. The aims of the experiment were to use morphological and molecular analysis to study the integration of the AtCO gene and its influence on agronomic traits in the T2 generation of Nipponbare transgenic AtCO rice. Morphological observations showed that agronomic traits tended to be better in the transgenic plants than in the wild type (controls), although the transgenic plants flowered later than the wild type. Polymerase Chain Reaction (PCR) analysis showed that 169 out of 227 transgenic rice plants showed hpt and CO gene integration.